Why Females Fight: Predicting Political Activism among Palestinian Female Youth - Spellings, Carolyn Reagh (2009)
A distinct focus on female youth experiences in political contests has been lacking in the literature on youth and political violence despite many female youth’s involvement with armed groups. The first Palestinian Intifada (1987-1993) saw the participation of many female youth alongside both teenage boys and men. This is notable especially given the patriarchal culture of Palestinian society in that women and young girls are traditionally confined to the private sphere. Additionally, public interactions with men and young boys could be viewed as improper and threats to one’s honor and purity may ensue. In light of these facts, the purpose of this study is to investigate the experience of Palestinian female adolescents in zones of political conflict - specifically in the Gaza Strip during the First Intifada. More specifically, this study explores the relationship between socioeconomic status, religious, political and individual characteristics on differences in levels of female participation and activist behaviors. Data were collected via self-report survey in the Gaza Strip in 1998 from a sample of 960 youth, 375 of which were female. Models predicting political involvement are assessed through hierarchical linear regression analyses. Results indicated that socioeconomic status, age, efficacy, religiosity, and political affiliation predicted Palestinian female youth activism in the first Intifada. No interaction was found between religiosity, political affiliation, and activism. These findings are discussed in relation to the broader literature on civic and political engagement of youth as well as gender issues in orthodox Islamic societies